Analyser l’expérience du stage en enseignement au travers du prisme des difficultés et des échecs de stagiaires québécois : réflexion basée sur les écrits spécialisés - Jean-François Desbiens; Adel Habak; Stéphane Martineau (Éducation et Socialisation)
This article presents a reflection about difficulties and failure sometimes experienced by student teachers during the teaching practicum. These phenomena are not well documented. In an experiential learning based approach, difficulties and failures are seen as part of a normal professional development process. Despite that, they are often perceived negatively through a failure avoidance fixed mindset while, on the opposite, those who adopt a growth mindset tend to consider them as learning occasions. Supported by the literature on failure based learning, we defend that a careful accompaniment provided by properly trained cooperative teachers and supervisors in problem solving might help student teachers cope more efficiently with difficulties and failure, and to build teaching competencies as well as teacher identity.